Provision of renal-specific nutrition knowledge for changing dietary practice in bangladeshi hemodialysis patients - Tanjina Rahman; Shakil Ahmed; Md. Ruhul Kabir; M. Akhtaruzzaman; Esrat Jahan Mitali; Harun-Ur Rashid; ZulfitriAzuan Mat Daud; Khor, Ban Hock; Deepinder Kaur; Pramod Khosla (Elsevier B.V., 2022)
Studies show that provision of nutrition knowledge help renal patients make informed food choices. This study aimed to evaluate the impact of nutrition knowledge for changing dietary practice among Bangladeshi dialysis Following development of a renal-specific nutrition booklet, a pilot study was conducted among 50 hemodialysis patients from a single dialysis setting. Demographic, anthropometric, clinical, biochemical, dietary data, and a 10-item MCQ on renal-specific nutrition information were collected before and 3 months after the provision of the booklet. 52%of the participants were male, 54% had twice weekly dialysis, age 53±12 years, and dialysis vintage was 46 ± 25 months. Serum potassium and phosphorous, dietary potassium, phosphorous, and phosphorous to protein ratio were significantly reduced after the provision of the booklet. Additionally, patients consuming >3 meals/day increased to 66% while adherence to renal-specific cooking method and vegetable preference were significantly increased to 70% and 62%, respectively. Provision of knowledge via renal-specific nutrition booklet was able to improve patients' dietary practice and enhance their dietary adherence to renal specific recommendations. Innovation: The booklet was developed using locally available food items in local language and was found beneficial in low-resource settings where overall health care facilities, including nutrition support are limited.